2015 International Conference on Electronics, Communications and Computers (CONIELECOMP) 2015
DOI: 10.1109/conielecomp.2015.7086933
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of QoS for intensive video traffic over 802.11e WLANs

Abstract: With the continuing development of the wireless technologies (Wi-Fi, 3G, 4G, WiMax and Bluethooth), the study of wireless multimedia transmissions has gained lately more attention. For example, the expectations of the company leaders on the growth of Wi-Fi video traffic has updated the lines of research on the standard IEEE 802.11e introduced to provide QoS (Quality of Service) to WLAN (Wireless LAN ) networks. A quantitative analysis has been performed by simulation. We use a node model EDCA (Enhanced Distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
2
13
0
3
Order By: Relevance
“…This study was conducted using QoS metric parameters such as packet delay variation, packet end-to-end delay and video traffic analysis to evaluate VC, E-mail, FTP and HTTP services using OPNET, and showed that the protocol that best suits VC is EIGRP. (Perez et al 2015) introduced a scenario to evaluate IEEE 802.11e standard for a number of videos, voice and best effort nodes, varying from 5 to 45 nodes, and showed an increase in average delay for these services. In addition, (Cahyadi et al 2019) produced a study investigates a comparison between Enhanced Distribution Channel Access (EDCA) against the "legacy" IEEE 802.11 Distributed Coordination Function (DCF) method for three traffic services e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study was conducted using QoS metric parameters such as packet delay variation, packet end-to-end delay and video traffic analysis to evaluate VC, E-mail, FTP and HTTP services using OPNET, and showed that the protocol that best suits VC is EIGRP. (Perez et al 2015) introduced a scenario to evaluate IEEE 802.11e standard for a number of videos, voice and best effort nodes, varying from 5 to 45 nodes, and showed an increase in average delay for these services. In addition, (Cahyadi et al 2019) produced a study investigates a comparison between Enhanced Distribution Channel Access (EDCA) against the "legacy" IEEE 802.11 Distributed Coordination Function (DCF) method for three traffic services e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, an integrated modeling approach for fault tolerant systems based on SAN has been used for the evaluation of systems performance parameters, such as re-liability, availability and maintenance costs [63]. Similarly, the Hierarchical Stochastic Activity Networks (HASN), an extension of SAN, has been used to quantitatively analyze the performance of QoS for intensive video traffic over the 802.11e standard used in WLANs [64]. SANs have also been used to analyse the performance of the KNXnet/IP congestion control mechanism [65].…”
Section: Petri Netsmentioning
confidence: 99%
“…_____________________________________________________________ 33 Higinio Alberto Facchini Análisis Comparativo de Prestaciones de Tráfico de Video multicast en Redes Heterogéneas H.264 es compatible con tres perfiles: línea base, principales, y extendida. Actualmente, el perfil de la línea de base y los perfiles principales están generando el mayor interés.…”
Section: Mpeg-4 Fue Iniciado Por La Iso Como Una Continuación Del éXunclassified
“…Los trabajos de investigación presentados en el apartado II.3.2, y otros relevantes [24][25][26][27][28][29][30][31][32][33][34][35][36] no discutidos por brevedad, muestran, en general, una falta de uniformidad de los escenarios de experimentación, en la cantidad y tipos de codecs, en los videos utilizados, etc.…”
Section: Ii35 Propuesta De Estudio Experimentalunclassified
See 1 more Smart Citation